Mickiewicz od świętych (zarysy hagiograficzne) = Mickiewicz of saints (hagiographic outlines) - Burta, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article concerns religious or rather hagiographic dimensions of Polish romantic literature. It presents Adam Mickiewicz's interests in the persons of saints, especially in St. Adalbert of Prague who is a character of a few unemotional and impersonal pieces of writings by Mickiewicz. At first sight it seems that the mentioned texts were written on request, they were official and they had an official and popularizing character. Especially circumstances of the origin of a biografic note entitled "Saint Adalbert" (1839), prepared for "Encyclopédie catholique", illustrate hues of the poet's motivation. It appears that in each text devoted to St. Adalbert (fragments of a dissertation "First centuries of Polish history" ["Pierwsze wieki historii polskiej"], 1838; lecture XIII of the first course of "Slavic literature" ["Literatura słowiańska"], 1841) Mickiewicz constantly attributes the authorhip of the hymn "Mother of God" ["Bogurodzica"] to the saint. The study brings an answer to the question why Mickiewicz wanted to sustain the XVI century legend about "Canticum sancti Adalberti" despite the fact that the legend's veracity was questioned in XIX century.
Keywords: Mickiewicz, Adam (1798-1855); św. Wojciech; "Bogurodzica"; Saint Adalbert; "Mother of God"